Does Canadian Multiculturalism Survive through State Repression?. Issue 3 (2nd July 2016) - Ryan, Phil
Abstract : Emma Ambrose and Cas Mudde argued in this journal that the absence of far-right parties in Canada can be attributed, among other factors, to "strong state repression of dissent" on multiculturalism policy. This article provides numerous examples of such dissent, to show that the state repression invoked by Ambrose and Mudde does not exist. The article also argues that certain "supply-side" explanations for the absence of a strong far-right apply to the Canadian case. It notes, in particular, how Steven Harper's Conservative government occupied much of the political space that might otherwise have been available for far-right challengers.